Clinical predictors of fever in stroke patients: relevance of nasogastric tube. (18th February 2015) - Muscari, A.; Puddu, G. M.; Conte, C.; Falcone, R.; Kolce, B.; Lega, M. V.; Zoli, M.
<x xml:space="preserve">Abstract</x> Objectives Fever frequently occurs in stroke patients and worsens their prognosis. However, only few studies have assessed the determinants of fever in acute stroke, and no study has specifically addressed the possible prediction of the development of fever. Materials and methods This investigation included 536 patients with acute stroke and a body temperature <=37°C during the first 24 h of stay. Ninety‐two of them (17.2%) subsequently developed fever (defined as a temperature >=37.5°C starting after 24 h). Among the clinical variables available during the first 24 h from admission, those predictive of the subsequent appearance of fever were searched for. One hundred further patients had a temperature >37°C during the first 24 h. Results In univariate analysis, many variables were predictive of the subsequent development of fever, but in multivariate analysis, only the following four predictors remained significant (odds ratio [95% confidence interval], P value): nasogastric tube (4.0 [2.2–7.4], <0.0001), atrial fibrillation (2.3 [1.4–3.8], 0.001), total anterior circulation syndrome (2.0 [1.2–3.5], 0.01), and urinary catheter (1.9 [1.1–3.3], 0.01). Among the 52 (9.7%) patients with three or four predictors, 31 (59.6%) subsequently developed fever. In addition, the factors independently associated with a temperature >37°C during the first 24 h were as follows: National Institutes of Health Stroke Scale (P < 0.0001), hemorrhagic stroke (P = 0.0008), atrial fibrillation (P = 0.002), and total parenteral nutrition (P = 0.03). Conclusions In patients with acute stroke, four clinical variables were found to be independently associated with the risk of developing fever and, of them, nasogastric tube was the strongest and most significant one.